Analisis Kecacatan Produk Pada Bracket Hanger Menggunakan Metode Failure Mode Effect Analysis di PT. Ravana Jaya - Chusnul Khotimah; Deny Andesta (Fakultas Teknik, 2022)
In the development of the modern industrial world today and product quality supervision is an activity that urgently needs to be carried out by every production activity in making products. Before the product is included in the storage warehouse, the finished product will be rechecked by the Quality Control section, seeing if the product is worth storing in the warehouse to be given to the customer. The purpose of this study is to calculate the highest Risk Priority Number (RPN) value, to find out what factors affect the occurrence of defects in the product, and provide proposed improvements to the production of Bracket Hanger products. The method used is Failure Mode Effect Analysis (FMEA). From the results of sorting the Risk Priority Number (RPN) an analysis will be carried out on each indicator value to find out which value has the greatest impact on the achievement of the RPN value. These results are used as a reference in providing product improvement proposals